Derivative Spectrophotometric Determination of Ruthenium(III) using Cinnamaldehyde Isonicotinoylhydrazone (CINH) - KIRAN KUMAR, V.; RAMESWARA RAO, M.; CHANDRASEKHAR, K.B.; DEVANNA, N. (Asian Journal of Chemistry, 2010)
Ruthenium(III) forms a brownish yellow coloured water soluble complex with cinnamaldehyde isonicotinoylhydrazone (CINH) reagent in acidic buffer pH 3.0 with λmax at 402 nm. The molar absorpitivity and Sandell's sensitivity is 1.25 × 104 L mol-1 cm-1 and 0.00809 μg/cm2, respectively. The Beers law validity range is 0.202 to 4.04 μg/mL. Ruthenium(III) forms (M:L) 1:1 complex with CINH and stability constant of the complex is 4.56 × 105. The developed derivative spectrophotomrtic method was employed for the determination of ruthenium(III) in synthetic samples of alloy and river water samples. The effect of various diverse ions have also been studied.